(untitled) (Global Journal of Science Frontier Research, 2017)
This study aimed at identifying of factors affecting market outlet choice of the smallholder mango producers in Boloso Bombe District, Southern Ethiopia. The survey was conducted in four randomly selected kebele administrations in the district. About 120 smallholder mango producers have been selected randomly from the four kebele administrations proportionally. Both qualitative and quantitative types of data were used. Sample households were used as source of the primary data used for the study. Both close ended and open ended (semi-structured) questionnaire was prepared to collect the data. Personal interview, focus group discussion and group discussions was used to capture adequate data. Both descriptive and inferential statistics were used to analyze the data. Multivariate probit model was used to identify factors affecting market outlet choices of the smallholder mango producers.